2016
DOI: 10.1128/aac.01064-16
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Novel Collagen Wound Model To Simulate the Activity and Distribution of Antimicrobials in Soft Tissue during Diabetic Foot Infection

Abstract: Diabetes has major implications for public health, with diabetic foot ulcers (DFUs) being responsible for significant morbidity and mortality. A key factor in the development of nonhealing ulcers is infection, which often leads to the development of biofilm, gangrene, and amputation. A novel approach to treating DFUs is the local release of antibiotics from calcium sulfate beads. We have developed a novel model system to study and compare the release and efficacy of antibiotics released locally, using collagen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
52
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(53 citation statements)
references
References 63 publications
(69 reference statements)
0
52
0
1
Order By: Relevance
“…The laboratory strains used in this study were the Nottingham Pseudomonas aeruginosa PA01, donated by Miguel Camara and the Staphylococcus aureus ATCC 6538 (LGC standards). Overnight cultures were prepared in tryptic soya broth (Oxoid) and diluted to 10 5 CFU/ml in fibroblast growth media (FGM) (Dulbecco Modified Eagle Medium (Sigma D5546 low glucose) supplemented with 10% fetal bovine serum (FBS)(Sigma), 80 mM HEPES (MP Biomedicals) and 4 mM glutamine (Sigma)) [40], 500 μl of diluted culture were used to inoculate models with S. aureus and P. aeruginosa as previously described [33]. Debrided tissue (DFAN, DFAL, DFAC) was sampled from three different subjects, weighed, and homogenised in a bead beater (Precellys) using glass beads until the tissue had completely homogenised.…”
Section: Bacterial Strains Media and Culture Conditionsmentioning
confidence: 99%
See 2 more Smart Citations
“…The laboratory strains used in this study were the Nottingham Pseudomonas aeruginosa PA01, donated by Miguel Camara and the Staphylococcus aureus ATCC 6538 (LGC standards). Overnight cultures were prepared in tryptic soya broth (Oxoid) and diluted to 10 5 CFU/ml in fibroblast growth media (FGM) (Dulbecco Modified Eagle Medium (Sigma D5546 low glucose) supplemented with 10% fetal bovine serum (FBS)(Sigma), 80 mM HEPES (MP Biomedicals) and 4 mM glutamine (Sigma)) [40], 500 μl of diluted culture were used to inoculate models with S. aureus and P. aeruginosa as previously described [33]. Debrided tissue (DFAN, DFAL, DFAC) was sampled from three different subjects, weighed, and homogenised in a bead beater (Precellys) using glass beads until the tissue had completely homogenised.…”
Section: Bacterial Strains Media and Culture Conditionsmentioning
confidence: 99%
“…When studying biofilms, investigators often look at lab strains of bacteria in monoculture using readily available substrates in the lab like plastic or agar because these studies can be carefully controlled and the methods and strains are well characterised [32,33], although some polymicrobial models of infection have been developed [34][35][36]. However, clinical isolates often behave differently to lab strains and there is evidence that polymicrobial biofilms have altered tolerance to antibiotics and form more robust biofilms with different architecture because of symbiotic interactions between the different species [35,37].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The 3D models of fibrous tissues can be engineered to recreate various stromal tissues, [27][28][29][30] and these can be adapted for wound models. Wound-like inclusions have been created during fabrication, [31][32][33][34] but this approach does not capture in vivo-like features of wounding, including retraction of the wound edge in tissues under tension. 35 To address these issues, Sakar and colleagues recently developed a 3D bioengineered wounding model, in which fibroblast/collagen tissues contract around anchoring pillars to form prestressed microtissues [36][37][38][39] that were then microsurgically injured using a robotically controlled micromanipulator.…”
Section: Introductionmentioning
confidence: 99%
“…So far, it is not confirmed that the application of various antimicrobials influences the mechanism of action of different biological therapies or the use of different devices. Instead, different models were generated for their collective use as collagen or sulfate beads for the local discharge of antimicrobials, which obtained positive results in the treatment of infection and scarring [149,150]. However, further investigations are required to guarantee that the activity of antimicrobials improves efficiency, in combination with other therapies, against the diverse microorganism populations found in DFU infections.…”
Section: Collateral Effects Of Antimicrobials In Different Dfu Therapiesmentioning
confidence: 99%